Structural and functional basis for starch binding in the SnRK1 subunits AKINβ2 and AKINβγ - Ávila-Castañeda, Alejandra; Gutiérrez-Granados, Natalia; Ruiz-Gayosso, Ana; Sosa-Peinado, Alejandro; Martínez-Barajas, Eleazar; Coello, Patricia (Frontiers in Plant Science, 2014)
Specialized carbohydrate-binding domains, the Starch-Binding Domain (SBD) and the Glycogen Binding Domain (GBD), are motifs of approximately 100 amino acids directly or indirectly associated with starch or glycogen metabolism. Members of the regulatory β subunit of the heterotrimeric complex AMPK/SNF1/SnRK1 contain an SBD or GBD. In Arabidopsis thaliana, the β regulatory subunit AKINβ2 and a γ-type subunit, AKINβγ, also have an SBD. In this work, we compared the SBD of AKINβ2 and AKINβγ with the GBD present in rat AMPKβ1 and demonstrated that they conserved the same overall topology. The majority of the amino acids identified in the protein-carbohydrate interactions in the rat AMPKβ1 are conserved in the two plant proteins. In AKINβγ, there is an insertion of three amino acids that creates a loop adjacent to one of the conserved tryptophan residues. Functionally, the SBD from AKINβγ and AKINβ2 could bind starch, but there was an important difference in the association when an amylose/amylopectin (A/A) mixture was used. The physiological relevance of binding to starch was clear for AKINβγ, because immunolocalization experiments identified this protein inside the chloroplast. SnRK1 activity was not affected by the addition of A/A to the reaction mixture. However, addition of starch inhibited the activity 85%. Furthermore, proteins associated with A/A and starch in an in vitro-binding assay accounted for 10 to 20% of total SnRK1 kinase activity. Interestingly, the identification of the SnRK1 subunits associated to the protein-carbohydrate complex indicated that only the catalytic subunits, AKIN10 and AKIN11, and the regulatory subunit AKINβγ were present. These results suggest that a dimer formed between either catalytic subunit and AKINβγ could be associated with the A/A mixture in its active form but the same subunits are inactivated when binding to starch.